2011
DOI: 10.1111/j.1365-2362.2011.02606.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of weight loss on C3 and C4 components of complement in obese patients

Abstract: Our findings show that in severely obese patients following a VLCD for 6 weeks produces reductions in factor C3, a biomarker of cardiovascular disease, and a significant improvement in some features of metabolic syndrome. In this way, the abovementioned diet may represent an effective strategy for treating obesity and related cardiovascular risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 40 publications
4
13
0
Order By: Relevance
“…Thus, C3 and ASP are increased in individuals with excess adiposity and with obesity [64]. Another study found that patients with BMI>35 kg/m2 took six weeks of very low calorie diet (VLCD), and it was observed circulating levels of C3 and BMI decreased [56]. Both of these confirm our speculation.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Thus, C3 and ASP are increased in individuals with excess adiposity and with obesity [64]. Another study found that patients with BMI>35 kg/m2 took six weeks of very low calorie diet (VLCD), and it was observed circulating levels of C3 and BMI decreased [56]. Both of these confirm our speculation.…”
Section: Discussionsupporting
confidence: 79%
“…It is well known that nutritional status is important for maintaining normal immune function. Worse nutrition status marked by a lower BMI will potentially lead to immune dysfunction including a decreased serum level of C3 [56]. Hence, we attempted to investigate the possible regulatory mechanisms between BMI and C3.…”
Section: Discussionmentioning
confidence: 99%
“…This may to some extent be interpreted as simple confounding since abdominal obesity is a known determinant of both IR and plasma C3 levels (3,(41)(42)(43). However, the relationship of waist circumference with C3 is not straightforward, because abdominal obesity may also be considered an ascending proxy in the causal pathway between C3 and IR (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Our group and others were able to demonstrate that the complement component 3 (C3) is one of the major determinants of the MetS [99,100,101] and postprandial lipemia in insulin resistant subjects, but also in insulin sensitive subjects [87,102,103]. C3 has also been genetically linked to the MetS in a recent meta-analysis of multiple genome wide association studies [104].…”
Section: Interplay Between Ffa Metabolism and Inflammation In Obesmentioning
confidence: 99%